2021
DOI: 10.1002/etc.5054
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Embryo‐Larval Exposure of Fathead Minnows to the Pharmaceutical Drug Metformin: Survival, Growth, and Microbiome Responses

Abstract: Metformin is a glucose-lowering drug commonly found in municipal wastewater effluents (MWWEs). The present study investigated the chronic effects of metformin in early-life stages of the fathead minnow (Pimephales promelas). Endpoints assessed were growth, survival, and deformities. The larval gut microbiome was also examined using 16 S ribosomal RNA gene amplicon sequencing to determine microbial community composition and alpha and beta diversity. Eggs and larvae were exposed to metformin measured concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 47 publications
(79 reference statements)
0
19
1
Order By: Relevance
“…Metformin is one of the most prevalent pharmaceuticals found in surface waters globally, and there is a growing body of evidence to suggest that current environmental exposure scenarios may adversely impact the reproduction and development of small-bodied fish. However, the nature and magnitude of effects appears to differ between species, timing of exposure, and study duration. ,,,,, , For example, the growth of 28-DPF Japanese medaka (Oryzias latipes) was found to be significantly reduced by developmental exposure to environmentally relevant concentrations of metformin. , Similar effects were not observed in 21-DPF FHM exposed to comparable concentrations of metformin as embryos; however, other researchers have found that the growth and reproduction of FHM are affected by environmentally relevant concentrations of metformin at later life stages. Exposure to nM concentrations of metformin also led to an increase in the occurrence of various morphological abnormalities in ELS zebrafish, along with behavioral alterations and changes in the proportion of unhatched eggs remaining at 5-DPF . The deformities observed in that study mirrored those observed in the present study, including skeletal abnormalities, cardiac edema, and yolk sac edema, with cardiac edema as the most frequently observed adverse outcome …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Metformin is one of the most prevalent pharmaceuticals found in surface waters globally, and there is a growing body of evidence to suggest that current environmental exposure scenarios may adversely impact the reproduction and development of small-bodied fish. However, the nature and magnitude of effects appears to differ between species, timing of exposure, and study duration. ,,,,, , For example, the growth of 28-DPF Japanese medaka (Oryzias latipes) was found to be significantly reduced by developmental exposure to environmentally relevant concentrations of metformin. , Similar effects were not observed in 21-DPF FHM exposed to comparable concentrations of metformin as embryos; however, other researchers have found that the growth and reproduction of FHM are affected by environmentally relevant concentrations of metformin at later life stages. Exposure to nM concentrations of metformin also led to an increase in the occurrence of various morphological abnormalities in ELS zebrafish, along with behavioral alterations and changes in the proportion of unhatched eggs remaining at 5-DPF . The deformities observed in that study mirrored those observed in the present study, including skeletal abnormalities, cardiac edema, and yolk sac edema, with cardiac edema as the most frequently observed adverse outcome …”
Section: Discussionmentioning
confidence: 99%
“…Despite the widespread environmental occurrence of metformin in aquatic systems, the effects of developmental metformin exposure on nontarget aquatic biota have not yet been fully elucidated. Laboratory studies have found that the nature and magnitude of effects of metformin exposure differ between species, timing of exposure, and study duration. , Moreover, important variations in sensitivity may also exist between laboratory and wild fish populations of the same species and life stage. These differences can be attributed to a number of factors that vary between natural and artificial habitats, including the nature and intensity of environmental stress, abiotic and biotic characteristics of the environment that interact with animals, whether the potential for avoidance exists, the influence of artificial and natural selection on traits within each population, and the fate and partitioning behaviors of aquatic contaminants that affect bioavailability (and thus, exposure and risk). Consequently, it is not uncommon for laboratory-derived water quality criteria and/or effect concentrations to under or overpredict toxicity for wild fish populations .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Translating these suborganismal effects into ecological consequences that can then give regulators (and the broader community) confidence in setting environmental limits for this group of compounds is likely to be the next big challenge, because there are many different mechanisms through which they may exert an effect. Even when no effects on fish larvae and microbiome composition are noted for commonly used pharmaceuticals such as metformin (Parrott et al, 2022), the fact that some of them are so prevalent in the environment warrants ongoing evaluation in other nontarget species, in environmental compartments, and at different scales, especially as new evaluation methodology becomes available.…”
Section: Introductionmentioning
confidence: 99%